Effect Of HRM Practices On Service Quality: Job Satisfaction As A Mediator Variable - Habtoor, N; Bin Zumrah, AR; Disomimba, MN; Samad, NSA (INT Organization Center Acad Research, 2024)
Indexed by WOS